2022
DOI: 10.1002/bse.3090
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental investments on green innovation: An integration of factors that increase or decrease uncertainty

Abstract: How institutional factors that increase or decrease uncertainty can influence the effect of environmental investments (EIs) on green innovation (GI) deserves further investigation. In this study, we first examine the direct impact of EIs on GI. Moreover, we consider political uncertainty (PU) as a factor that increases uncertainty and consider marketization degree (MD) and environmental regulations (ERs) as two other factors that decrease uncertainty; then, we examine the effects of these factors on EIs and GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 95 publications
(182 reference statements)
0
4
0
Order By: Relevance
“…We collect data on listed companies' export sales from WIND. We obtain patent data from the Chinese Research Data Services Platform (CNRDS) to construct the measure of green innovation (Li, Xu, & Ramanathan, 2022). Information on export destinations is gathered from the General Administration of Customs of P. R. China (GAC), information on political risk is gathered from the International Country Risk Guide (ICRG) (Datta, Musteen, & Basuil, 2015), buyer sophistication is based on the Global Competitiveness Report published by the World Economic Forum 1 (Hasija et al, 2020), and China Stock Market & Accounting Research (CSMAR) is the information source for measuring state ownership.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…We collect data on listed companies' export sales from WIND. We obtain patent data from the Chinese Research Data Services Platform (CNRDS) to construct the measure of green innovation (Li, Xu, & Ramanathan, 2022). Information on export destinations is gathered from the General Administration of Customs of P. R. China (GAC), information on political risk is gathered from the International Country Risk Guide (ICRG) (Datta, Musteen, & Basuil, 2015), buyer sophistication is based on the Global Competitiveness Report published by the World Economic Forum 1 (Hasija et al, 2020), and China Stock Market & Accounting Research (CSMAR) is the information source for measuring state ownership.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…The degree of marketization arises from a series of economic, social, legal, and political institutional reforms. These reforms not only reflect the relationship between the government and the market in a region, but also represent the extent to which the market influences resource allocation (Li, Xu, & Ramanathan, 2022; Li, Long, et al, 2022). To test whether the degree of marketization affects the role of corporate digital transformation on ESG performance.…”
Section: Further Analysismentioning
confidence: 99%
“…Albitar et al (2022) defend the relevance of innovation in the field of climate change, and observe how environmental technology, linked to better climate governance, reduces CO 2 emissions. In contrast, Li, Xu, et al (2022) emphasized the importance of institutional factors that can influence environmental investments like green innovation.…”
Section: Climate Governance and The Disclosure Of Information On Clim...mentioning
confidence: 99%
“…Albitar et al (2022) examined environmental innovation with CO 2 emissions along with the controlling effect of environmental governance and argued that the environmental technology with better environmental governance reduces the CO 2 emission, which leads to the positive signals towards the analysts that disclose firms' environmental‐related strategies in their discussion. In contrast, Li, Xu, and Ramanathan (2022) emphasized the importance of institutional factors that can influence environmental investments like green innovation. The empirical results in the context of China indicated that environmental innovations positively influence green innovation along with its utility that's creates green environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%